1972
DOI: 10.1159/000230903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrocortisone on Immunoglobulin Synthesis and Secretion by Human Peripheral Lymphocytes <i>in vitro</i>

Abstract: Human peripheral lymphocytes in tissue culture synthesize immunoglobulin Ig which is secreted into the medium. The small amounts of Ig produced can be detected in nanogram quantities by a modification of the ammonium sulfate test. Ig formation by peripheral human lymphocytes was affected by hydrocortisone when the cells were briefly exposed to the hormone at the onset of incubation. When hydrocortisone was dissolved in culture medium or when the more soluble hydrocortisone-21-sodium succinate was employed, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

1973
1973
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…The effect of in vitro CSs on Ig production is variable depending on a number of experimental parameters (3). For example, in certain systems, in vitro Ig production is enhanced by the presence of CS in culture (34)(35)(36)(37). The CS-induced potentiation of the SAC-stimulated PFC responses is in agreement with these previously noted observations.…”
Section: Discudsionsupporting
confidence: 86%
“…The effect of in vitro CSs on Ig production is variable depending on a number of experimental parameters (3). For example, in certain systems, in vitro Ig production is enhanced by the presence of CS in culture (34)(35)(36)(37). The CS-induced potentiation of the SAC-stimulated PFC responses is in agreement with these previously noted observations.…”
Section: Discudsionsupporting
confidence: 86%
“…In the pokeweed mitogen (PWM)-~:lriven Ig synthesis by cultured lymphocytes, physiological as well as supraphysiological doses of glucocorticoids have an enhancing property, provided that they are present at the beginning of the culture (Fauci et al 1977;Cooper et al 1979;Brieva et al 1983). In addition, Ig production can be induced by glucocorticoids in lymphocytes cultured in vitro in the presence of fetal calf serum (FCS), without the addition of any other mitogen (Smith et al 1972;Grayson et al 1981 ;Orson et al 1983). FCS seems to be required for this stimulating effect (Sierakowski and Goodwin 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In young chickens, treatment with cortisone resulted in the mobilization of B lymphocytes from the Bursa and enhanced the differentiation into mature immunoglobulin secreting plasma cells in the peripheral lymphoid tissues (8). Several in vitro studies of immunoglobulin production by human lymphocytes have also revealed a stimulatory effect of steroids (9,10). In some instances where suppressor cells are known to be present, steroids appear to enhance in vitro immunoglobulin synthesis, and this response has been thought to reflect inactivation or inhibition of suppressor cell function (11,12).…”
Section: Introductionmentioning
confidence: 99%